Discarded COVID‐19 masks‐derived‐doped porous carbon for lithium‐sulfur batteries. (18th September 2022) - Rong, Qian; Yuwen, Chao; Liu, Peng; Cheng, Feixiang; Xia, Shubiao
Summary: Despite the high theoretical capacity and energy density of lithium‐sulfur (Li‐S) batteries, the development of Li‐S batteries has been slow due to the poor electrical conductivity and the shuttle effect of the electrode materials, resulting in low sulfur utilization and fast long‐term cycling capacity decay. The modified carbon materials are often used as sulfur hosts to significantly improve the cycling performance of the materials, but also bring high‐cost issues. Here, the porous carbon materials are synthesized quickly and conveniently by the microwave cross‐linking method using discarded medical masks as carbon sources and concentrated sulfuric acid as solvent. However, poor surface and structural properties limit the application of materials. The porous carbon material is modified with p‐toluene disulfide and urea as the sulfur and nitrogen sources by the microwave cross‐linking method, which not only improves the porosity and specific surface area of the porous carbon material, but also improved the electrical conductivity and interlayer spacing of the material. As synthesized SN‐doped porous carbon is employed as the sulfur host, which exhibits a high discharge capacity (1349.3 mAh g −1 ) at 0.1°C, the S‐porous C/S, N‐porous C/S, and SN‐porous C/S can maintain 78.1, 43.9, and 59.5% of the initial capacity after 500 cycles. The results indicate that the doping of S and N atoms provides sufficient active sites for the chemisorbed lithium polysulfides (LiPSs) to improve the reaction kinetics of the materials. Abstract : Schematic diagram of production of functionalized waste COVID‐9 mask‐based porous carbon.